The Influence of Plating Technique and Incubation Temperatureon Bacterial Count from Fish and Fishy Products - THAMPURAN, NIRMALA; IYER, H KRISHNA; IYER, K MAHADEVA (Fishery Technology, 2017)
For bacterial sampling of raw unprocessed fish and frozen fishery products, spreadplate method is preferable to pour plate method; incubation of plates at 30Â°C gives a higher count than incubation at 37Â°C. Analysis of variance of the data shows thatsample variation between different types of fishes is highly significant whereasthe variations between triplicate plates is not significant at 5 % level.